PVC handbook - Wilkes, C. E. (Charles E.).; Summers, J. W. (James W.).; Daniels, C. A. (Charles Anthony), 1943-; Berard, Mark T., 1961- (Munich, Germany : Hanser Publishers, 2005)
'In this single handbook, the editors aim to give a diverse audience of readers a complete account of all aspects of PVC from monomer manufacture to polymerization; the gamut of such additives as stabilizers, lubricants, plasticizers, impact modifiers, fillers and reinforcing agents; blends and alloys; compounding and processing; characterization; combustion resistance and weatherability; product engineering design; applications; environmental and safety; and finally the PVC industry dynamics.''The handbook contains both practical formulation information as well as a mechanistic view of why PVC behaves as it does.'--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Polyvinyl chloride -- Handbooks, manuals, etc